Gestão democrática sob cerco : a tecnologia de gestão educacional "elitizando" a escola cidadã integral na Paraíba - Chagas, Liliane Alves (2024)
The Full-Time Education Program of the State of Paraíba has an educational management model designed by a private organization, the Institute of Co-responsibility for Education (ICE). This model is called Educational Management Technology (TGE), and has been adopted in full-time schools in Paraíba’s education network since 2015, when the model was created. The question that constituted our research problem was: do the guidelines for school management proposed by TGE in Vocational Citizen Schools (Ecit) promote democratic management in these school communities? The general objective was to analyze how TGE conceives democracy and the democratic management that should be implemented in the Ecits of the state network of Paraíba. To this end, the research, with a qualitative approach in education, was developed using the case study as a method of procedure. Its exploratory nature, as well as document analysis and bibliographical research, was fundamental for the investigative, analytical, and qualitative treatment of findings from interviews with members of the school Community. The interviews followed the ethical procedures necessary for their completion. In addition, it uses the Policy Cycle Approach (Bowe; Ball; Gold, 1992) and the Theory of Policy Enactment (Ball; Maguire; Braun, 2021) combined with Discourse Theory (Laclau; Mouffe, 2015) as its theoretical-methodological framework, since we rely on an understanding of politics as discourse. This theoretical-methodological tool will be used to broaden the discussions, in the search for analysis and understanding of the discourses constituted by the actors of the policy under investigation. Our analysis found that the school management that has been mobilized by the TGE in the Citizen Schools in Paraíba is not in line with the democratic management proposed by Brazilian educational legislation, given that in addition to the absence of mechanisms that enable the democratic choice of principals and principals, we see that the concept of neoliberal democracy that underlies the model has acted in an attempt to weaken collegiate, representative, deliberative and democratic spaces, such as the school council, and we also see the subjects acting from a perspective of tutelage participation, since their participation in decision-making processes within the Ecit is not effective. However, we advocate the existence of acts of resistance and (re)existences that contradict and subvert what is proposed by the ICE.